Pengalaman Mahasiswa Keperawatan dalam mempelajari Caring - Sri Mujiyanti; Ani Haryani; Dini Rachmaniah (Universitas Faletehan, 2022)
Professional value is needed in professional nursing practice. Caring plays an important role for nursing students in providing nursing intervention to clients. The purpose of the study was to determine the phenomenon of the student learning process of caring to improve their caring competence. The study used a descriptive qualitative design of phenomenology. The number of participants was 15 students, both at the academic and internship levels. Convenience sampling and analysis content were used to analyze data. The result of this study found three themes with eight categories. The first theme, caring was focused on physical, psychological, social, and spiritual conditions aimed at patient’s healing. The second theme, caring was influenced by themselves, family, and the learning environment. The Third theme students need competent lecturers, adequate facilities, and good learning strategies to improve their caring competence. Learning that focuses on increasing students' caring competence become a need felt by nursing students. Lecturers and faculty need to review the existing curriculum and curriculum tools to ensure that these needs are met.